KEBERHASILAN E-SATISFACTION DAN E-REPURCHASE INTENTION BUKALAPAK: PERAN DIGITAL MARKETING, E-SERVICE QUALITY DAN E-TRUST - Novie Zaraswati; Irma Setyawati (Jurnal Ilmiah Global Education, 2023)
This study aims to analyze the effect of Promotion, Service Quality, and E-Trust, on the E-Repurchase Intention and E-Satisfaction of Bukalapak Consumers. Data analysis in this study used the Structural Equation Modeling (SEM) analysis method using AMOS 22. The use of Structural Equation Modeling analysis examines in detail the influence between variables. This study uses a survey method, measuring variables by distributing google forms to 150 respondents. The results showed that digital marketing, e-service quality, and e-trust have a direct and significant effect on e-repurchase intention and e-satisfaction. In this study, the role of variables is very significant. The intervening variable, namely e-repurchase intention, successfully mediates. Digital marketing variables, e-service quality, and e-trust have a direct and significant effect on e-repurchase intention through e-satisfaction. The managerial implication of this research is the importance of Buka Lapak online stores in optimizing marketing. digital marketing, e-service quality, and e-trust that make consumers feel satisfied and more familiar with e-commerce. The higher the satisfaction that customers get, the more buying interest will appear. Buyers who feel satisfied will increase repurchase interest. Consumer trust can lead to a sense of satisfaction and interest in buying back through e-commerce.